EFEKTIVITAS PENERAPAN MODEL PEMBELAJARAN THINK PAIR SHARE MELALUI MACROMEDIA FLASH 8 TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA - Mhd. Rinanda; Muhammad Syahril Harahap; Rahmad Fauzi (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2022)
This study aims to determine the effectiveness of the Think Pair Share (TPS) cooperative learning model through Macromedia Flash 8 on the mathematical communication skills of students in SMA Negeri 1 Tambangan. This research is an experimental study with a one group pretest post test design. The population of the study involved all students of class X SMA Negeri 1 Tambangan with a total of 55 students. The research sample was obtained using a cluster sampling technique, namely class X MIA with 27 students. The research instrument was a test of mathematical communication skills and an observation sheet for learning activities. The data analysis used is descriptive analysis and inferential statistics. Based on descriptive analysis, it was found that (1) the average value of the application of the TPS learning model through macromedia flash 8 was 3.20 (good category) and (2) the average value of students' mathematical communication skills on the system of linear equations of two variables material before using the TPS learning model through macromedia flash 8 is 67.08 (enough category) and after using the TPS learning model through macromedia flash 8 is 84.16 (very good category). Furthermore, the acquisition of the N-gain index value of the students' mathematical communication ability is 0.50 (medium category). (3) Based on inferential statistics using paired samples test, (SPSS version 20) gives a significant score of 0.000 which is smaller than the alpha 0 real level. 0.05 (0.000 < 0.05) which means that the use of the TPS learning model through Macromedia Flash 8 on the mathematical communication skills of class X SMA Negeri 1 Tambangan is effective. Thus, it is concluded that the application of the TPS learning model through macromedia flash 8 for improving students' mathematical communication skills is quite effective.